MicroRNA expression profile of a Malaysian Bajau family with familial mitochondrial neurogastrointestinal encephalomyopathy - Yong, F.L.; Wang, C.W.; Tan, K.S. (Fundacao de Pesquisas Cientificas de Ribeirao Preto, 2015)
Mitochondrial neurogastrointestinal encephalomyopathy (MNGIE) is a rare, autosomal recessive disorder associated with mutations in the thymidine phosphorylase (TYMP) gene. The main objective of this study was to characterize the genetic profiles of the deceased proband’s family members (N = 4) using DNA sequencing and to determine miRNA deregulation in MNGIE using miRNA microarray profiling and bioinformatic analysis. We found that the genetic profile of the younger sister showed similar TYMP gene mutations as that of the proband with the exception of a heterozygous mutation in exon 10. The miRNA microarray revealed 55 significantly up-regulated and 65 significantly down-regulated miRNAs. These miRNAs have been implicated in various mitochondrial dynamics such as energy metabolism, Krebs cycle, mitochondria-associated apoptosis, and mitophagy. In conclusion, we demonstrate that blood miRNAs are deregulated in the pathogenesis of MNGIE and these changes may have therapeutic implications. Further experimental studies will be required to elucidate the functional miRNA-mRNA interactions in MNGIE.